Early Korean literature : selections and introductions - McCann, David R. (David Richard), 1944- (Columbia University Press, 2000)
Preeminent scholar and translator David R. McCann presents an anthology of his own translations of works ranging across the major genres and authors of Korean writing--stories, legends, poems, historical vignettes, and other works--and a set of critical essays on major themes. A brief history of traditional Korean literature orients the reader to the historical context of the writings, thus bringing into focus this rich literary tradition. The anthology of translations begins with the Samguk sagi, or History of the Three Kingdoms, written in 1145, and ends with "The Story of Master Hô," written in the late 1700s. Three exploratory essays of particular subtlety and lucidity raise interpretive and comparative issues that provide a creative, sophisticated framework for approaching the selections.